2012
DOI: 10.1055/s-0032-1316801
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Protocol for the Hiyama Cross-Coupling Reaction Catalyzed by Palladium on Carbon

Abstract: Abstract:A method for the palladium on carbon (Pd/C) catalyzed cross-coupling reaction between aryl halides and trialkoxy(aryl)silanes in the presence of a small amount of water is established using tris(4-fluorophenyl)phosphine as the ligand. A range of biaryl compounds is prepared using this protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Various biaryl compounds have been synthesized using this protocol [Eq. (19)] ,. Moreover, the same group found that this catalytic system still works when the tris(4‐fluorophenyl)phosphine is replaced by acetic acid.…”
Section: Applications Of Pd/cmentioning
confidence: 99%
“…Various biaryl compounds have been synthesized using this protocol [Eq. (19)] ,. Moreover, the same group found that this catalytic system still works when the tris(4‐fluorophenyl)phosphine is replaced by acetic acid.…”
Section: Applications Of Pd/cmentioning
confidence: 99%
“…In this way, a facile bond breaking of the carbon-silicon bond during transmetalation is favored. It was demonstrated that alkali metal salt such as NaF or CsF could also act as silane activators for Hiyama coupling reactions (Gurung et al 2013;Monguchi et al 2012). In addition, both ammonium-and phosphonium-based ionic liquid have been proved to be good extractants of Pd suggesting their complexing ability (Katsuta et al 2011;Regel-Rosocka et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of new molecules with improved properties is of current importance. Therefore, including halides in the aromatic system, in particular iodine, results in very important intermediates for the synthesis of more complicated molecules, since it allows a wide range of reactions such as Sonogashira, 24 Suzuki, 25 Stille, 26 Heck, 27 Hiyama, 28 Negishi, 29 etc. Preparation of compounds with groups such as iodine are of a high synthetic value and a wide variety of reactions can be performed.…”
Section: Resultsmentioning
confidence: 99%